Immunohistochemical Evaluation of E- Cadherin in Oral Epithelial Dysplasia and Oral Squamous Cell Carcinoma - Gupta Aashi (Wolters Kluwer Medknow Publications, 2024)
BackgroundCancers arising in the oral cavity are more commonly of squamous cell carcinomas. E-cadherin is a calcium-dependant transmembrane glycoprotein of the type-1 cadherin superfamily is an invasion/tumor suppressor gene, which plays a vital role in epithelial cell-cell adhesion. Epithelial E-cadherin expression loss increases tumor invasiveness and metastasis. AimTo determine the expression of E-cadherin in oral epithelial dysplasia (OED) and oral squamous cell carcinoma (OSCC). Materials and MethodsAnalysis of E-cadherin expression in 10 cases of normal mucosa, 15 cases of various grades of OED, 15 cases of OSCC. Statistical AnalysisThe data were calculated using Chi-square test and analysis of variance test (ANOVA). ResultsAn intragroup comparison of staining intensity and staining location for OED showed a highly significant difference between mild and moderate grade (P < 0.001). A significant difference of staining intensity was noted among well and moderately differentiated grades, and well and poorly differentiated grades of OSCC. A comparison of staining location among well and poorly differentiated grades of OSCC was found to be significant. ConclusionExpression loss is observed as the severity of the lesion progresses in both OSCC and OED. The increased loss of expression in oral squamous cell carcinoma poorer the prognosis.